Induction of ubiquitin-conjugating enzymes during terminal erythroid differentiation. - Wefes, I (1995)
A global cellular reorganization occurs during the reticulocyte stage of erythroid differentiation. This reorganization is accomplished partly through programmed protein degradation. The selection of proteins for degradation can be mediated by covalent attachment of ubiquitin. We have cloned cDNAs encoding two ubiquitin-conjugating (E2) enzymes, E2-20K and E2-230K, and found their genes to be strongly induced during the differentiation of erythroblasts into reticulocytes. Induction of the E2-20K and E2-230K genes is specific, as transcript levels for at least two other ubiquitinating enzymes fall during erythroblast differentiation. In contrast to most proteins induced in reticulocytes, E2-20K and E2-230K enzymes are present at strongly reduced levels in erythrocytes and thus decline in abundance as reticulocyte maturation is completed. This result suggests that both enzymes function during the reticulocyte stage, when enhanced protein degradation has been observed. These data implicate regulated components of the ubiquitin conjugation machinery in erythroid differentiation.